Information Security Analysis Using ITIL Framework in Domain Operation Services - Anastasya Putri Maramis, Clara Kristianti Rondonuwu, Steva Ngantung, (International Journal of Information Technology and Education, 2022)
Information is one of the important assets for related companies/agencies. Information Security is the protection of information from various kinds of threats that can damage, disrupt, and reduce the performance of a company/related agency. Information security at SMK Negeri 1 Kakas currently has to be very carefully considered because if information can be accessed by irresponsible people, the accuracy of the information will be doubted and will even cause other problems. The purpose of this study is to measure or analyze how large and safe the level of information security in the State Vocational High School 1 Kakas is. The method used in this research is the Information Technology Infrastructure Library version 3 (ITIL V3) method. ITIL is a set consisting of Service Design, Service Transition, Service Operation. In this case the author focuses on Service operation. The results of this study indicate that the level of information security is good, privacy can be maintained, risk management is not good, and there is good trust in all parties in SMK Negeri 1 Kakas.